Widespread transcript shortening through alternative polyadenylation in secretory cell differentiation - Larry C. Cheng (Nature Portfolio, 2020)
Alternative polyadenylation generates multiple mRNA isoforms with different 3′ UTR sizes. Here the authors report global 3′ UTR shortening that is coupled to increased expression of secretory pathway genes in secretory cell differentiation.